University Students' Perceptions of Online Learning during COVID-19 Pandemic (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
The Covid-19 pandemic has seriously affected all social systems, including education in Nepal. After the government decided to implement lockdowns throughout the country, all schools and universities remained closed for a long time. To overcome the loss of education from long-term lockdowns, most of the universities of Nepal sought to continue education by using digital platforms as well as they could. The purpose of the study reported here was to examine university students' perceptions of online learning during the pandemic and identify the challenges they face while learning through online mode in rural and semi-urban areas of Nepal. Using a cross-sectional online survey design, I collected data from 8 community campuses of rural and semi-urban areas of Nepal. The participants for this study were 100 master's degree students who had been learning through various online platforms since the lockdown began. Eight of those participants were interviewed to explore their perceptions of using online learning. The result showed that the majority of the students found online learning supportive during the pandemic and they preferred the continuity of online learning even after the Covid-19 pandemic. However, they faced challenges related to technology, pedagogical skills, and the socio-economic status of the students. Based on these findings, this article argues that the effectiveness of online teaching can only be further studied by considering the effects of these other social-educational factors simultaneously. कोभिड-१९ महामारीले समाजका सबैखाले कृयाकलापमा असर गर्यो, जसमा शिक्षा अछुतो रहेन । नेपलामा सरकारले विद्यालय र विश्वविद्यालयबन्द राख्ने निर्णय गर्यो जुन भ्याक्सिन अभावका कारण निकै लामो समयसम्म रह्यो । त्यसका कारण भएको खतीलाई न्यूनीकरण गर्दै धेरैजसोविश्वविद्यालयहरुले डिजिटल खालहरुको प्रयोग गरेर सकेसम्म शिक्षलाई निरन्तरता दिन प्रयत्न गरे । यो लेखमा प्रस्तुत अन्वेषणको उद्देश्यअन्लाइन शिक्षणप्रति विश्वविद्यालयका विद्यार्थीको बुझाईलाई अध्ययन गरी उनीहरुले सामना गरेका चुनौतीलाई पहिचान गर्नु थियो ।अन्तर्खण्डीय अन्लाइन सर्भे प्रयोग गरेर गाउँ र अर्धशहरीय क्षेत्रका ८ वटा सामुदायिक कलेजबाट आँकडा जम्मा गरिएको थियो । सहभागीहरुमा१०० जना स्नाकोत्तर तहका विद्यार्थी थिए जसले विभिन्न अन्लाइन खालहरुमार्फत अध्ययन गरिरहेका थिए । तीमध्ये ८ जनालाई अन्तर्वार्ता लियो। यो अध्ययनले अन्लाइन सिकाई सहयोगी पाएका थिए भने महामारीपछि पनि यसको प्रयोगमा निरन्तरता होस भन्ने चाहना व्यक्त गरे । तरउनीहरुले प्रविधिको प्रयोगमा चुनौती भएको, अध्यापकहरुमा भएको प्रविधि मार्फत गरिने शिक्षणमा कमी भएको, र आफ्नो सामाजिक-आर्थिकस्तरका कारण अरु समस्या खप्नु परेको अनुभव पनि बताए । त्यसका आधारमा यो लेखले नेपालजस्ता समाजमा यी सामाजिक-शैक्षणिकअवस्थाको विश्लेषण एकैसाथ गरेर मात्र अनलाइन शिक्षा कति प्रभावकारी छ भन्ने खोजी अघि बढाउन सकिन्छ भन्ने तर्क गरेको छ ।